Synthesis, characterization and thermal studies on solid compounds of 2-chlorobenzylidenepyruvate of heavier trivalent lanthanides and yttrium(III) - Bannach, G.; Schnitzler, E.; Treu, O.; Utuni, VHS; Ionashiro, Massao [UNESP] (Springer, 2006)
Solid-state compounds of general formula LnL(3)center dot nH(2)O, where Ln represents heavier lanthanides and yttrium and L is 2-chlorobenzylidenepyruvate, have been synthesized. Chemical analysis, simultaneous thermogravimetry-differential analysis (TG-DTA), differential scanning calorimetry (DSC), X-ray powder diffractometry, elemental analysis and infrared spectroscopy have been employed to characterize and to study the thermal behaviour of these compounds in dynamic air atmosphere.On heating these compounds decompose in four (Gd, Tb, Ho to Lu, Y) or five (Eu, Dy) steps. They lose the hydration water in the first step and the thermal decomposition of the anhydrous compounds up to 1200 degrees C occurs with the formation of the respective oxide, Tb4O7 and Ln(2)O(3) (Ln=Eu, Gd, Dy to Lu and Y) as final residue. The dehydration enthalpies found for these compounds (Eu, to Lu and Y) were: 65.77, 55.63, 86.89, 121.65, 99.80, 109.59, 131.02, 119.78, 205.46 and 83.11 kJ mol(-1), respectively.
Keywords: benzylidenepyruvate; rare earth; thermal behaviour